Manajemen Pendidikan Keluarga dalam Penanaman Karakter Jujur untuk Anak Usia Sekolah Dasar - Saepullah, Asep; Anshorullah, Arich Hawary; Maulana, Agus; Ardiansyah, Muhammad Nurman; Santika, Nina Dwi Ayu; Sudrajat, Suryati; Shajaratuddar, Shajaratuddar; Kania, Imas (Diversity: Jurnal Ilmiah Pascasarjana, 2022)
Character education has recently attracted the attention of the public. This is due to anxiety about the shift in moral values, especially among the youth as a generation of future leaders of the nation. The emergence of various events in society that describe the behavior of teenagers, acts of corruption, and so on are considered to have injured the noble values of the Indonesian nation. This is what raises awareness of how important it is to build character education in the world of education. Character education is something that must be developed, so it is very necessary for community participation in the formation of children’s character. In this case, school is a place to develop children’s character. Character development can be done through learning and extra-curricular activities. Character education in schools apart from exemplary teachers is also very important related to management and management in schools. Because the management referred to here is how a character education institution can be planned, controlled, and implemented in educational activities in schools that are already adequate.